"Too Posh to Push": The Rise and Rise of a Catchphrase. Issue 4 (December 2013) - Weaver, Jane; Magill‐Cuerden, Julia
Abstract Background The phrase "too posh to push" was coined over 14 years ago to describe maternal request for cesarean section in the absence of clinical indications. The phrase was readily taken up and used by the United Kingdom media despite limited evidence that many women request cesarean sections or have an aversion to vaginal birth. The objectives of this study were to explore the way in which the phrase was used; the context and themes associated with it. Methods To better understand the part the news media might play in public and health care professionals' perceptions, all articles using the phrase in eight UK national weekday newspapers from 1999 to 2011 (n = 335) were subjected to content analysis. Results Key themes have changed over the years but some themes, such as celebrity cesareans, the risks of cesarean section, and the rising cesarean rate, have remained. Four different definitions of the term "too posh to push" were identified. Levels of usage of these terms changed over time. Misinterpretation of the National Sentinel Cesarean Section Audit results and a tendency to confuse elective cesarean section with maternal request for a cesarean have suggested that more "too posh to push" cesareans occurred than is probably the case. Conclusion The phrase seems to have become well established. It is likely that press handling of the topic has continued to contribute to the impression that cesarean purely for maternal request is common. The association with celebrity continues to fuel press interest in the topic.